2018
DOI: 10.1371/journal.pone.0193749
|View full text |Cite
|
Sign up to set email alerts
|

Mycophenolic acid induces senescence of vascular precursor cells

Abstract: ObjectiveEndothelial dysfunction is central to the pathogenesis of many rheumatic diseases, typified by vascular inflammation and damage. Immunosuppressive drugs induce disease remission and lead to improved patient survival. However, there remains a higher incidence of cardiovascular disease in these patients even after adequate disease control. The purpose of this study was to determine the effect of mycophenolic acid (MPA), a commonly used immunosuppressive drug in rheumatology, on blood vessel or circulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 52 publications
1
10
0
Order By: Relevance
“…Senescence is the state of irreversible cell-cycle arrest, which is part of the normal cellular aging process and a response to a variety of stresses. MPA induce senescence in chronic myeloid leukemia cell lines [ 56 ], vascular precursor cells [ 37 ], and DMSC, as we reported here. The role of senescence as a general response to physiologic stress seems increasingly important.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Senescence is the state of irreversible cell-cycle arrest, which is part of the normal cellular aging process and a response to a variety of stresses. MPA induce senescence in chronic myeloid leukemia cell lines [ 56 ], vascular precursor cells [ 37 ], and DMSC, as we reported here. The role of senescence as a general response to physiologic stress seems increasingly important.…”
Section: Discussionsupporting
confidence: 81%
“…The activation of the G2 checkpoint provides an opportunity for DNA repair. MPA treatment causes cell cycle arrest in G0/G1 in lymphocytes and vascular precursor cells [ 37 ]. The arrest of the cell cycle after DNA damage can also be induced at S or G2 phases, depending on the cell type, its active checkpoint mechanism, as well as its growth conditions [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[14] Additionally, IMPDH inhibitors can cause the appearance of senescence markers. [15] Whether lowering pyrimidine ribonucleotide pools also triggers the onset of premature senescence is not clear in the literature. Nevertheless, recent evidence suggests that CTPS blockage could turn on a senescence-like program by triggering profound changes in cell-cycle progression.…”
Section: Changes In Nucleotide Pools Influence Cell Fatementioning
confidence: 99%
“…In addition to the paper cited in our article, a recent publication by Go et al demonstrated a crucial role for mycophenolic acid in the senescence of endothelial cells and endothelial dysfunction. ( 4 )…”
mentioning
confidence: 99%